1994
DOI: 10.3171/jns.1994.80.1.0133
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model of posttraumatic syringomyelia: the role of adhesive arachnoiditis in syrinx formation

Abstract: An experimental model was devised to elucidate the role of spinal blockade in posttraumatic syringomyelia. Thirty-eight Japanese White rabbits, each weighing about 3 kg, were used in this study. The animals were divided into four groups: in Group 1, eight animals received traumatic injury only; in Group 2, 12 animals received traumatic injury following injection of 100 mg kaolin suspended in 1 cc normal saline solution into the subarachnoid space at the site of trauma; in Group 3, nine animals received traumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 15 publications
1
55
0
1
Order By: Relevance
“…The review of standard X-rays, taken at the time of this study, showed kyphosis in 60% of the cases (45), with a mean angle of 18.28 (5 ± 808), equal or greater to 308 in 36% of the cases (27). The percentage of spinal canal stenosis measured by CT scan re¯ects the quality of the reduction ( Figure 5).…”
Section: Radiological Analysis Of the Lesion Sitementioning
confidence: 73%
See 2 more Smart Citations
“…The review of standard X-rays, taken at the time of this study, showed kyphosis in 60% of the cases (45), with a mean angle of 18.28 (5 ± 808), equal or greater to 308 in 36% of the cases (27). The percentage of spinal canal stenosis measured by CT scan re¯ects the quality of the reduction ( Figure 5).…”
Section: Radiological Analysis Of the Lesion Sitementioning
confidence: 73%
“…The contusion was most often visualised (27 cases ie 36%), followed by syrinxes (21 cases 27.5%) showed a non statistical signi®cance. The occurrence of a syrinx had no correlation with the initial extent of the lesionsyndrome, this being on average 3.6 levels in the absence of a syrinx as opposed to 4.5 levels with a syrinx.…”
Section: Spinal Cord Pathologies ®Ndings On Mrimentioning
confidence: 88%
See 1 more Smart Citation
“…Processes postulated to be involved include: 'slosh and suck' at the site of injury, liquefaction, development of hematoma, a malacic change in the spinal cord, necrosis, enzymatic lysis, tissue loss and arachnoiditis. 7,8 Several studies have been sought to identify clinical and radiological factors associated with post-traumatic syringomyelia. Factors examined include: age at onset, gender, cause of injury, site of injury, severity of injury, type of vertebral fracture, treatment method and the degree of encroachment into the vertebral canal.…”
Section: Introductionmentioning
confidence: 99%
“…4 Edgar and Quail emphasised the role of the tethered cord in both forms of PTMs. 3 Many works have confirmed the causal link between arachnoiditis and syrinx 15,16 or myelomalacic myelopathies. 17 In our study, all of the patients had spinal lesions that were located at the subaxial cervical spine or at the thoracolumbar junction.…”
Section: Discussionmentioning
confidence: 99%